Occupational stress in nursing teachers: An integrative literature review (Research, Society and Development, 2021)
The teaching profession of higher education is characterized by overloads, intense changes and pressures that lead to several consequences. To identify the causes of occupational stress in nursing professors. It is integrative literature review, in the Latin American Literature in Health Sciences databases (LILACS) and in the Nursing Database (BDENF). Articles published by the health area, in Portuguese, from 2009 to May 2020, complete with free and online access. A total of 06 articles were identified. The discussions presented by the authors were described in two categories. This study results in the following factors and/or situations that generate stress: working conditions; ethical issues; intense mental load; lack of professional recognition; theoretical-practical classes; association of teaching and health services; interpersonal relationship; family/social, financial and health situations and among the main complications: stress, anxiety, insomnia and sleep difficulties, headache, vascular failure, pain, tiredness, edema, among other problems. The study showed the diversity and complexity of diagnosing stressors, as well as the health complications of higher education faculty.